BIOLOGICAL LEARNING MATERIAL: DETECTION OF FLAVONOID FROM THE LEAF OF JACK FRUIT ( Artorpus altilis Park.) - METI INDROWATI; C. J. SOEGIHARDJO (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
This research aimed to detect the flavonoid content from the leaf ofjack fruit (Artocarpus altilis Park). That leaf has medicinal aspect, since it can be used to decrease the glucose from the blood circulation and act as anti diabethic activity respectively. The detection of flavonoid was carried out by using thin layer chromatography (TLC) with steady phase of silica of GF 254 and the elluent ratio of chloroform: methanol of 98:2. The result obtained the presence of flavonoid complexes at that leaf indicated by yellow spot and amoniac steam on the TLC.. That result could enrich the biochemistry learning material toward student.